Pengaruh Persentase Pemegang Saham Lama, Reputasi Auditor, Reputasi Underwriter, Umur Perusahaan, Jenis Industri, dan reputasi Emiten Terhadap Initial return di Bursa efek Indonesia - Fiki Kartika (Solusi: Jurnal Kajian Ekonomi dan Bisnis, 2013)
This study is a replication of previous studies. This study examined the effect of non-accounting information includes the percentage of existing shareholders, auditor reputation, underwriter reputation, the age of the company, type of industry. The thing that distinguishes this study from previous research that this study uses the issuer’s reputation as a non-accounting information. The issuer’s reputation is a strategic asset, because reputation can increase the value of the company concerned. Therefore, the problem arises is whether the non accounting information includes the percentage of existing shareholders, auditor reputation, underwriter reputation, the age of the company, type of industry, and affect the reputation of the issuer’s initial return on the Indonesia Stock Exchange. Results of this study demonstrate that the percentage of existing shareholders, the auditor’s reputation, the reputation of underwriters, company age, type of industry, and affect the reputation of the issuer’s initial return.